RELASI FUZZY PADA GRUP FAKTOR FUZZY - Ahmad Madani; Saman Abdurrahman; Na'imah Hijriati (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2020)
Fuzzy subsets on the non-empty set is a mapping of this set to the interval . The concept of fuzzy subgroups introduced from advanced concept of fuzzy set in group theory. In concept of fuzzy set there is the concept of relations is fuzzy relations. In this study examined that fuzzy relations related to the equivalence and congruence on a fuzzy group and fuzzy factor group. The results of this study was to show that a fuzzy relation    if  and    if  is a fuzzy congruence relations on fuzzy group and a fuzzy relation  defined of is a fuzzy congruence relations on fuzzy factor group.